2024
DOI: 10.1186/s12870-024-04747-9
|View full text |Cite
|
Sign up to set email alerts
|

Variation of antibacterial and antioxidant secondary metabolites and volatiles in leaf and callus extracts of Phulai (Acacia Modesta Wall.)

Noura Sh. A. Hagaggi,
Usama M. Abdul-Raouf,
Tarek A. A. Radwan

Abstract: Background Acacia species are economically significant as medicinal plants that have been utilized since ancient times. Acacia modesta has been reported to possess potent antibacterial and antioxidant properties, but its growth rate is slow. In this study, we hypothesized that inducing callus in vitro from A. modesta could enhance the production of antibacterial and antioxidant secondary metabolites, thereby circumventing the issues of slow growth and excessive harvesting of the plant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Spitaler et al [8] reported that the biosynthesis of phenolic compounds is enhanced in plants growing at high altitudes. Jin et al [26,27] reported that the levels of total phenolics and antioxidant activity in red wine signi cantly increase with the altitude at which the grape plants are grown.…”
Section: Discussionmentioning
confidence: 99%
“…Spitaler et al [8] reported that the biosynthesis of phenolic compounds is enhanced in plants growing at high altitudes. Jin et al [26,27] reported that the levels of total phenolics and antioxidant activity in red wine signi cantly increase with the altitude at which the grape plants are grown.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolites' antibacterial and antimicrobial properties have the potential to be useful in the treatment of a variety of infectious diseases that are resistant to current antibiotics. This could enhance our efforts to provide alternative medical treatments, particularly in developing countries where access to healthcare is limited [18]. The primary active compound present in the extract of Microbispora sp.…”
Section: Discussionmentioning
confidence: 99%